Date palm fruit (var. Ajwa) promotes proliferation of human bone marrow mesenchymal stem cells: potential natural booster for endogenous stem cells growth - Masniza, M. L.; Hayati, A. R.; Wirda, A. A. Asral; Fariha, M. M. Nur; Zetty Nadia Mohd Zain; Nur Syahrina Rahim; Fadlul Azim Fauzi Mansur (Int Soc Horticultural Science-Ishs, 2024)
Fruits, The International Journal of Tropical and Subtropical Horticulture Fruits 75 (4) 161-169 ISSN 0248-1294 print and 1625-967X online